2008
DOI: 10.1086/590210
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with Clumping Factor A and Fibronectin Binding Protein A to PreventStaphylococcus aureusInfection of an Aortic Patch in Mice

Abstract: Staphylococcus aureus is a leading cause of ventricular assist device–related infections. This study evaluated the protective effect against S. aureus infection of active and passive immunization that targeted 3 proteins involved in bacterial attachment to a murine intra-aortic polyurethane patch. Active immunization of mice with a combination of the A domains of clumping factor A (ClfA), fibronectin-binding protein A (FnBPA) and fibronectin-binding protein B or passive immunization with monoclonal antibodies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
34
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 15 publications
1
34
0
Order By: Relevance
“…C, surface plot of SEB shows mutated residues (red color) which are distinct from D the MHC surface (rotating 180 degrees around vertical axis) shows in cyan (residues 43, 44, 45, 46, 47, treatment of viral diseases including rabies and SARS, combination of mAbs against wild-type epitope and variant epitope can prevent the emergence of escape variants (47,48). Moreover several studies have shown that targeting more than one adhesion protein with mAb in S. aureus infection can be beneficial (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…C, surface plot of SEB shows mutated residues (red color) which are distinct from D the MHC surface (rotating 180 degrees around vertical axis) shows in cyan (residues 43, 44, 45, 46, 47, treatment of viral diseases including rabies and SARS, combination of mAbs against wild-type epitope and variant epitope can prevent the emergence of escape variants (47,48). Moreover several studies have shown that targeting more than one adhesion protein with mAb in S. aureus infection can be beneficial (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the many surface proteins and virulence factors of S. aureus, many of which have been evaluated as potential vaccine targets (6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Current and past S. aureus vaccines or therapeutic antibody strategies have focused mainly on capsular polysaccharide (CPS), virulence factors, surface proteins, and iron-regulated proteins.…”
mentioning
confidence: 99%
“…The leading candidate of this type of vaccine is StaphVAX, a bivalent polysaccharide and protein-conjugated vaccine (16,17). Other strategies for developing S. aureus vaccines have targeted virulence factors and surface proteins, including alpha-toxin (a nontoxic derivative of H35L) (7,18), clumping factor A (ClfA) (19), fibronectin binding protein A or B (FnBPA or FnBPB) (12), Panton-Valentine leukocidin (PVL) (20), and protein A (11). Iron-regulated proteins, such as Merck V710, which is based on iron-regulated surface determinant B (IsdB) (6,21), have also been investigated as other possible targets for vaccines against S. aureus.…”
mentioning
confidence: 99%
“…Several vaccine candidates have shown various levels of success in animal models (for reviews, see references 2 and 3). Clumping factor A (ClfA), an adhesin that can adhere to both fibrinogen and fibronectin, demonstrated some level of protection in sepsis (4,5), arthritis (5,6), prosthetic device infection (7), and mastitis (8) models. The fibrinogen-binding domain of ClfA (amino acids 40 to 559) is responsible for ligand binding.…”
mentioning
confidence: 99%
“…The fibrinogen-binding domain of ClfA (amino acids 40 to 559) is responsible for ligand binding. The entire domain and a slightly truncated version of the domain (amino acids 40 to 531) have been shown to elicit protection in animal models (5,7,9,10). A vaccine including a ClfA antigen based on the fibrinogen-binding domain fragment is currently in clinical trials (11,12).…”
mentioning
confidence: 99%